A new cryptic Cnemaspis Strauch (Squamata: Gekkonidae) from an isolated granite hill on the Mysore Plateau, Karnataka, India - Khandekar, Akshay; Thackeray, Tejas; Agarwal, Ishan (Zootaxa, 2020)
We describe a cryptic new species of the Cnemaspis mysoriensis complex from an isolated rocky hillock near Yadiyur, Mandya District of south Karnataka, India. Cnemaspis stellapulvis sp. nov. can be diagnosed from all other peninsular Indian congeners by its small body size (SVL <32 mm), presence of spine-like tubercles on the flanks, heterogeneous dorsal pholidosis, two or three femoral pores on each thigh separated on either side by eight poreless scales from a continuous series of two precloacal pores in males, tail with enlarged, strongly keeled, conical tubercles forming whorls, median row of sub-caudals smooth and slightly enlarged, and a distinct colour pattern. The new species can be diagnosed from members of C. mysoriensis clade by the number of femoral and precloacal pores and number of poreless scales separating these series, the number of dorsal tubercles rows at mid-body, the number of ventral scales across the belly at mid-body and subtle colour pattern differences; besides 13.4–21.4 % uncorrected ND2 sequence divergence. In this paper, we define the Cnemaspis mysoriensis clade and provide a diagnosis and comparison against peninsular Indian congeners. We also provide major diagnostic characters for members of the C. mysoriensis clade. The discovery of yet another endemic species of Cnemaspis from one of the many isolated granite rocky hills on Mysore Plateau highlights the possibilities of presence of many more cryptic undescribed species.